Neuroprotective Effects of Albizia lebbeck (L.) Benth. Leaf Extract against Glutamate-Induced Endoplasmic Reticulum Stress and Apoptosis in Human Microglial Cells - Onuma Phoraksa; Chanika Chimkerd; Parunya Thiyajai; Kunchit Judprasong; Siriporn Tuntipopipat; Tewin Tencomnao; Somsri Charoenkiatkul; Chawanphat Muangnoi; Monruedee Sukprasansap (MDPI AG, 2023)
Endoplasmic reticulum (ER) stress caused by excessive glutamate in the central nervous system leads to neurodegeneration. Albizia lebbeck (L.) Benth. has been reported to possess neuroprotective properties. We aimed to investigate the effect and mechanism of A. lebbeck leaf extracts on glutamate-induced neurotoxicity and apoptosis linked to ER stress using human microglial HMC3 cells. A. lebbeck leaves were extracted using hexane (AHE), mixed solvents, and ethanol. Each different extract was evaluated for cytotoxic effects on HMC3 cells, and then non-cytotoxic concentrations of the extracts were pretreated with the cells, followed by glutamate. Our results showed that AHE treatment exhibited the highest protective effect and was thus selected for finding the mechanistic approach. AHE inhibited the specific ER stress proteins (calpain1 and caspase-12). AHE also suppressed the apoptotic proteins (Bax, cytochrome c, cleaved caspase-9, and cleaved caspase-3); however, it also increased the antiapoptotic Bcl-2 protein. Remarkably, AHE increased cellular antioxidant activities (SOD, CAT, and GPx). To support the activation of antioxidant defense and inhibition of apoptosis in our HMC3 cell model, the bioactive phytochemicals within AHE were identified by HPLC analysis. We found that AHE had high levels of carotenoids (α-carotene, β-carotene, and lutein) and flavonoids (quercetin, luteolin, and kaempferol). Our novel findings indicate that AHE can inhibit glutamate-induced neurotoxicity via ER stress and apoptosis signaling pathways by activating cellular antioxidant enzymes in HMC3 cells, suggesting a potential mechanism for neuroprotection. As such, A. lebbeck leaf might potentially represent a promising source and novel alternative approach for preventing neurodegenerative diseases.